2021
DOI: 10.7861/clinmed.2021-0037
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID symptoms reported at asynchronous virtual review and stratified follow-up after COVID-19 pneumonia

Abstract: BackgroundThe COVID-19 pandemic has strained healthcare systems and how best to address post-COVID health needs is uncertain. Here we describe the post-COVID symptoms of 675 patients followed up using a virtual review pathway, stratified by severity of acute COVID infection. MethodsCOVID-19 survivors completed an online/telephone questionnaire of symptoms after 12+ weeks and a chest radiograph. Dependent on findings at virtual review, patients were provided information leaflets, attended for investigations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 30 publications
1
27
0
1
Order By: Relevance
“…We also found the symptom burden not to be related to characteristics of the previous hospital stay, particularly the severity of COVID-19, which goes along with data from shorter follow-up times in previous studies [36,61,[63][64][65]. In some studies, however, a positive correlation between the severity of the COVID-19 disease and the symptom burden at follow-up had been found [15,26,35,58,60,66].…”
Section: Discussionsupporting
confidence: 83%
“…We also found the symptom burden not to be related to characteristics of the previous hospital stay, particularly the severity of COVID-19, which goes along with data from shorter follow-up times in previous studies [36,61,[63][64][65]. In some studies, however, a positive correlation between the severity of the COVID-19 disease and the symptom burden at follow-up had been found [15,26,35,58,60,66].…”
Section: Discussionsupporting
confidence: 83%
“…For example, Huang et al ( 3 ) also reported that fatigue or muscle weakness and sleep difficulties were the most common symptoms at the 6-month follow-up. In another study, Taylor et al found that at an average 18 weeks post-acute infection, the COVID-19 survivors had a median of two ongoing physical complaints, with fatigue the most common ( 44 ). All these data illustrate that the majority of COVID-19 survivors suffer from at least one ongoing symptom at 3–6 months follow-up, with fatigue and sleep difficulty the most frequently reported symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological symptoms included: (1) anosmia [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ] (2) dysgeusia [ [11] , [12] , [13] , [15] , [16] , [17] , [18] ] (3) headache [ 11 , [13] , [14] , [15] , [16] , 18 , 21 , 22 ] (4) any cognitive dysfunction [ 13 , 14 , 16 , [18] , [19] , [20] , [21] ] (see: Supplemental Table 2) (5) any fatigue [ 11 , 13 , 14 , 16 , 18 , 19 , [21] , [22] , [23] , [24] , [25] ] (fatigue/malaise [ 11 , 13 , 14 , 16 , 18 , 19 , [21] , [22] , [23] ], chronic fatigue syndrome [ 24 ], post exertional malaise [ 21 ]) (6) pain (neuropathic pain [ 15 , 23 ], myalgia [ 11 , 12 , [14] , [15] , [16] , 18 , 21 , …”
Section: Methodsmentioning
confidence: 99%